Investigación de mercados. Impacto de nuevas tendencias en el consumo de complementos nutricionales (2015)
As for food, in recent years has seen a growing trend towards the consumption of healthy alternatives, and enrichment of the diet through nutritional supplements, this paper presents an analysis of the market of nutritional supplements focused on Quinoa. Thus, it scanning from a general perspective the globally trend of nutritional supplements consumption, through the review of secondary data from reliable sources such as Euromonitor. Plus, it presents the results of a quantitative market research that consisted of a personal survey of 230 people in the city of Cali, in order to validate whether the globally trend that was revised through secondary data, was also valid for this local market. Finally, to deepen the theme, It has been made qualitative research conducted to seven key industry people, and the instrument used was an in-depth interview, these people are members of the middle part of the value chain, for example managers of pharmaceutical and manufacturing companies that have some direct or indirect relationship with the major input studied.